UJI AKTIVITAS ANTIHIPERGLIKEMIK EKSTRAK ETANOL DAUN KETAPANG (Terminalia catappa L) PADA MENCIT PUTIH YANG DIINDUKSI ALOKSAN - Jena Hayu Widyasti; Dian Marlina; Avianti Eka Dewi A.P Eka Dewi A.P (Jurnal Farmasi Indonesia, 2016)
Diabetes mellitus is a chronic disease that caused of decreasing insulin production at Pancreatic β cell or insulin production which not effective. The purpose of this research was proving catappa’s leaves extract (Terminalia catappa L) have an activity to decrease blood glucose levels trough diabetics on effective doses. The prominent goal may achieved was obtaining efficacious natural medicine of anti-diabetes and knowing the effective doses of catappa’s leaves extract (Terminalia catappa L) as anti-diabetes. This Anti-hyperglycemic research is using mice as many as 30 mice. The activity experiment of anti-diabetes was executed to 6 treatment groups, there are Group I (normal control), Group II negative control (alloxan induced 180 mg/kgBW and aquadest), Group III (alloxan induced and catappa’s leaves extract 75 mg/kgBW), Group IV (alloxan induced and catappa’s leaves extract 150 mg / kgBW), Group V (alloxan induced and catappa’s leaves extract 300 mg/kgBW), and Group VI (positive control that given by alloxan induced and glibenclamide 10mg/kgBW). All of the treatment group was given with that treatment for 14 days and were carried measurement of blood glucose levels on days 0, 3, 10, 17. The leaf extract anti-diabetes activities shown by calculating hypoglycemic capacity of each treatment. The result of this research showed that the ethanol extract of catappa’s leaves have anti-hyperglycemic activities on mice that alloxan induced. At the doses of ethanol extract of leaves of catappa 300 mg/kgBW have effectively anti-hyperglycemic activities than doses of 150 mg/kgBW and 75 mg/kgBW that was comparable with positive control group